Insights into the anaphase-promoting complex: a molecular machine that regulates mitosis - Chang, Leifu; Barford, David (Current opinion in structural biology, 2014)
•Assignment of the complete secondary structure and subunit identification of the APC/C.•Mechanism of D box and KEN box recognition by APC/C-coactivator complexes.•Mechanism of stimulation of APC/C E3 ligase reaction by coactivator.•Principles of APC/C inhibition by regulators through blocking degron recognition and inhibiting ubiquitination reactions. The anaphase-promoting complex/cyclosome (APC/C) is a large multimeric complex that functions as a RING domain E3 ubiquitin ligase to regulate ordered transitions through the cell cycle. It does so by controlling the ubiquitin-mediated proteolysis of cell cycle proteins, notably cyclins and securins, whose degradation triggers sister chromatid disjunction and mitotic exit. Regulation of APC/C activity and modulation of its substrate specificity are subject to intricate cell cycle checkpoints and control mechanisms involving the switching of substrate-specifying cofactors, association of regulatory protein complexes and post-translational modifications. This review discusses the recent progress towards understanding the overall architecture of the APC/C, the molecular basis for degron recognition and ubiquitin chain synthesis, and how these activities are regulated.